Závažné kraniotrauma v dětském věku: význam včasné ofenzivní terapie - Knor, J; Pekara, J; Pavlíček, P (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2022)
The case report presents the case of a five-year-old boy who fell off a scooter and sustained a blow to the left temporal region of his head. During a CT examination in the district hospital he suddenly showed a deterioration in the level of consciousness. Subsequent treatment along with transport to a specialized department were aimed at preventing secondary pathological changes and maintaining pressure-volume homeostasis of the brain. High-quality controlled ventilation with effective pharmacotherapy and gentle transport were essential. At the target specialized department, cerebral oedema in the left temporal region and aspiration in the right upper lung lobe were identified. The boy was extubated after 6 hours of controlled ventilation and discharged to an intermediate care bed two days later without any serious consequences. Key words: cerebral oedema, haemodynamic swelling, severe head injury.
Keywords: lidé; mužské pohlaví; Male; předškolní dítě; Brain Edema; Brain; Craniocerebral Trauma; Child, Preschool; edém mozku; mozek; kraniocerebrální traumata; Humans